Smart Societies: From Citizens as Sensors to Collective Action - Monroy-Hernández, Andrés; Farnham, Ph.D., Shelly D.; Kiciman, Emre; Counts, Scott; De Choudhury, Munmun (interactions, 2013)
Social media has become globally ubiquitous, transforming how people are networked and mobilized. This forum explores research and applications of these new networked publics at individual, organizational, and societal levels.